Political Machines and the Institutional Background of Economic Miracles. Issue 2 (20th April 2021) - Popa, Mircea
Abstract: Some of the world's most notable economic miracles were accompanied by corruption, rent-seeking and clientelism, which is puzzling given the wide agreement on the importance of good institutions for growth. This article builds on the experiences of the US, Japan, Italy, South Korea and China to argue that these institutional maladies can be the natural outcomes of governance structures that facilitate growth. The theoretical argument revolves around the nature and strategies of dominant political organizations. Party machines can sometimes broker compensatory transfers that allow entrenched interests to profit from economic change, rather than be hurt by it, by the logic of the political Coase theorem. Transfers which are inefficient in most settings can therefore, if properly rationed and targeted, alleviate some of the key strategic impediments to growth identified by the political economy literature.